Are all types of capital flows driven by the same factors? Evidence from Mexico - Raúl Ibarra-Ramírez; Téllez-León Isela-Elizabeth (Banco de México, 2017)
In this paper we analyze the impact and persistence of shocks to global (push) and domestic (pull) factors on each component of the financial account for the Mexican Balance of Payments at the highest degree of disaggregation, including investment by foreign residents in Mexican public and private sector securities, as well as investment by domestic residents in foreign securities. To this end, we estimate impulse response functions from vector autoregressive models for the period 1995-2015. We find that an increase in the foreign interest rate leads to lower portfolio investment, particularly in Mexican public sector securities. An increase in global risk generates lower portfolio investment, particularly in private sector securities. Foreign investors respond to a higher extent to foreign interest rate and liquidity shocks compared to domestic investors.
Keywords: F21; F32; F41; F47; 330; Capital Flows; Push Factors; Pull Factors; Vector Autoregression